(untitled) (Geospatial Health, 2023)
In the Article titled "Detecting space-time disease clusters with arbitrary shapes and sizes using a co-clustering approach." published November 6th, 2017, in Vol 12(2) of Geospatial Health, an author’s name was misspelled. The fifth author’s name should be "Alamgir". Reference: Ullah S, Daud H, Dass SC, Khan HN, Khalil A, 2017. Detecting space-time disease clusters with arbitrary shapes and sizes using a co-clustering approach. Geospatial Health, 12:567. https://doi.org/10.4081/gh.2017.567